Protective activity of galacto-oligosaccharides against intestinal damage and inflammation induced by enterotoxigenic Escherichia coli F4+ and evaluation of prebiotic potential - Guantario, Barbara; Tanghe, Sofie; Finamore, Alberto; Devriendt, Bert; Devirgiliis, Chiara; Verstringe, Stefanie; Rooyackers, Enya; De Vos, Maartje; Vande Ginste, Jan; Roselli, Marianna (Frontiers in Veterinary Science, 2026)
Post-weaning diarrhea in piglets is frequently caused by enterotoxigenic Escherichia coli (ETEC) F4+. The objective of this study was to examine the possible protective effect of galacto-oligosaccharides (GOS) on ETEC F4+-induced intestinal injury. Growth inhibition of ETEC F4+ in the presence of 2% GOS was assessed, as well as the ability of GOS to reduce pathogen adhesion and invasion in the intestinal Caco-2 cell line. GOS ability to counteract ETEC F4+ adhesion was also assessed ex vivo in piglet small intestinal villi. Protective activity of GOS against ETEC F4+-induced membrane damage in Caco-2 cells was evaluated through transepithelial electrical resistance (TEER), phenol red apparent permeability (Papp) and immunolocalization of tight junction proteins occludin and ZO-1. Inflammation was assessed by quantification and immunolocalization of phosphorylated-p65 protein, indicative of NF-κB activation. Finally, GOS prebiotic activity on probiotic strains Lactobacillus amylovorus: ATCC 33198 and DSM 16698, as well as Limosilactobacillus reuteri subsp. porcinus DSM 110571, was also investigated. The results showed that GOS significantly reduced ETEC F4+ adhesion and invasion in Caco-2 cells, as well as adhesion to piglet intestinal villi. Furthermore, GOS markedly decreased ETEC F4+ induced membrane damage, as evidenced by improvement of TEER, phenol red Papp and tight junction protein immunolocalization. A reduction of p65 phosphorylation and nuclear translocation in the presence of GOS indicated a diminished activation of the NF-κB pathway. GOS also exhibited promising prebiotic activity toward the tested probiotic strains. Taken together, these in vitro findings suggest the potential of including GOS in piglet weaner diets to prevent ETEC F4+-induced intestinal injury.